Role of FGF15 in Hepatic Surgery in the Presence of Tumorigenesis: Dr. Jekyll or Mr. Hyde? - Albert Caballeria-Casals; Marc Micó-Carnero; Carlos Rojano-Alfonso; Cristina Maroto-Serrat; Araní Casillas-Ramírez; Ana I. Álvarez-Mercado; Jordi Gracia-Sancho; Carmen Peralta (Cells, 2021)
The pro-tumorigenic activity of fibroblast growth factor (FGF) 19 (FGF15 in its rodent orthologue) in hepatocellular carcinoma (HCC), as well as the unsolved problem that ischemia-reperfusion (IR) injury supposes in liver surgeries, are well known. However, it has been shown that FGF15 administration protects against liver damage and regenerative failure in liver transplantation (LT) from brain-dead donors without tumor signals, providing a benefit in avoiding IR injury. The protection provided by FGF15/19 is due to its anti-apoptotic and pro-regenerative properties, which make this molecule a potentially beneficial or harmful factor, depending on the disease. In the present review, we describe the preclinical models currently available to understand the signaling pathways responsible for the apparent controversial effects of FGF15/19 in the liver (to repair a damaged liver or to promote tumorigenesis). As well, we study the potential pharmacological use that has the activation or inhibition of FGF15/19 pathways depending on the disease to be treated. We also discuss whether FGF15/19 non-pro-tumorigenic variants, which have been developed for the treatment of liver diseases, might be promising approaches in the surgery of hepatic resections and LT using healthy livers and livers from extended-criteria donors.